Assessing Public Awareness of Circular Economy in Indonesia: Insights from Google Trends Data - Geusan Akbar, Gugun (International Journal of Social Science, Education, Communication and Economics, 2024)
This study aims to understand public interest and awareness of the circular economy in Indonesia by analyzing Google Trends search volumes for keywords over the past five years, from 2017 to 2022: "Waste Recycling," "Circular Economy," "Waste Management," and "Waste Reduction." Data analysis shows that "Waste Recycling" consistently has the highest and most stable search volume, especially in regions such as South Sulawesi, North Kalimantan, and West Sulawesi, indicating successful local campaigns. In contrast, "Circular Economy" has significantly lower search volumes, even in metropolitan areas, suggesting that this concept is relatively new. Interest in "Waste Management" varies, with higher volumes in South East Sulawesi, East Nusa Tenggara, and Central Sulawesi, highlighting the importance of waste management but also the need for better policy and infrastructure support. "Waste Reduction" has the lowest search volume, indicating the need for intensive educational efforts. Geographical analysis shows significant regional differences, with high-interest areas serving as education centers and low-interest areas needing targeted interventions. This study underscores the necessity for robust educational campaigns, supportive policies, and stakeholder collaboration to enhance the adoption of circular economy practices. These insights inform policy development and the design of effective educational campaigns for environmental sustainability in Indonesia